Summer mungbean for doubling farmer’s income and livelihood security - Kumar, Rajesh; Singh, Atar; Nath, C P; Tripathi, C M; Praharaj, C S; Dubey, S K; Singh, N P (Indian Farming, 2020)
Increasing the land productivity with highly intensive cropping system is the need of the day to meet the growing demand of food grain. Rice-wheat and maize-wheat systems contributing the major share in food grain production are now facing the problem of decline in factor productivity with reduction in farm income. Introducing summer mungbean after harvesting of wheat is a potential option for increasing system productivity and long-term sustainability in these cereal based production systems. India accounts for 79% (11.65 million ha) of the total rice fallows of South Asia (15.0 million ha). Rice fallows are mainly spread in the states of Andhra Pradesh, Assam, Bihar, Chhattisgarh, Jharkhand, Madhya Pradesh, Odisha, West Bengal, and Uttar Pradesh. These states are embedded with one of the extensive agro-production systems of South Asia. Therefore, increasing cropping intensity with mungbean cultivation to ensure higher yield with a sustainable ecosystem will be a great service.